An exploration of nursing home staff perceptions of the impact of infection prevention and control champions in Ireland: A descriptive qualitative study - Richard Byrne; Maura Smiddy (Journal of Infection Prevention, 2026)
Background The COVID-19 pandemic highlighted the need for robust Infection Prevention and Control (IPC) policies and for the workforce of long-term residential care facilities (LTRCFs) to be educated and trained in IPC with support from specialists with IPC knowledge and advice. IPC champions are often put in place within LTRCFs to provide education and guidance. The aim of this study was to explore how the impact of trained IPC champions (or leads) was perceived by staff in the long-term residential care settings. Methods Purposive sampling was conducted to recruit participants from three LTRCFs located in the East of Ireland. Semi-structured interviews were conducted amongst six participants which were then transcribed and analysed using thematic analysis. Results Four themes were identified via codes and sub-themes: (1) IPC Core Knowledge and Skills, (2) Point of Care Coaching and Support, (3) Practical Enablers of IPC and (4) Audit and Quality Improvement in IPC . Conclusion The results indicate that IPC champions make a positive impact on IPC practices and procedures in Irish LTRCFs. The identified themes and sub-themes indicate that IPC champions’ roles are multi-faceted, and that they utilise several skills to ensure best IPC practices are carried out in their workplace.